Transparency And Accountability Of Hajj Funds from the Perspective Of Fiqh Muamalah - Rara Genta Munggarani Basri; Muhammad Faishal Hidayat; Muhammad Hadi Nurfajar (JURNAL ILMU SYARIAH, 2025)
The management of Hajj funds is a significant mandate with religious, social, and economic dimensions, and therefore requires the application of high transparency and accountability principles. This study aims to analyze the transparency and accountability of Hajj funds from the perspective of fiqh mu’amalah, by emphasizing sharia principles such as trust, justice, openness (transparency), and accountability. The research method is qualitative, with a normative approach, based on a literature review of the Qur'an, Hadith, fiqh rules, and legislation governing the management of Hajj funds. The results showed that in fiqh mu’amalah, the management of Hajj funds must be based on a clear contract, the use of funds in accordance with their allocation, and the disclosure of information to the pilgrims as shahibul maal. Transparency and accountability are not only administrative requirements but also Syar'i obligations that aim to maintain the benefit of the Ummah and prevent irregularities (mafsadah). Thus, applying the principles of transparency and accountability in the management of Hajj funds aligns with the values of fiqh mu’amalah and is key to building public trust and ensuring professional, sharia-compliant management. Keywords: Transparency; Accountability; Hajj Funds; Fiqh Muamalah; Islamic Financial Management